Representasi Keresahan Yang Dirasakan Oleh Perempuan Dalam bentuk Karya Seni Lukis - Eveanna, Caitlin; Pemayun, Tjokorda Udiana Nindhia; Gulendra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
Women have a big role in everyday life, making them face various obstacle and responsibilities. However, women are often underestimated as objects that must look perfect in society. Behind that, women actually feel various anxieties that they feel almost every day. Starting from the pain of menstruation, the pressure of beauty standards that disturbs the mind at all times to the objectification of women. These three things have a significant impact on women. Many women feel insecure, anxious and even depressed because of things like this. Women also often feel uncomfortable when they want to do activities outside the home because of the many incidents of objectification of women out there. Women continue to be required to be the figure that society expects without caring about what women actually feel about these actions and demands. In creating this work, the author raised this issue to make it into a work of painting by exploring symbols to represent and visualize the anxiety experienced by women. By using various symbols of simple things encountered in daily life, the author represents this anxiety experienced in a painting. The author also uses the plaque technique as a technique in making paintings.